Penerbitan Sertifikat Hak Milik Atas Tanah Asli Tapi Palsu Pada Kantor Pertanahan Kota Jayapura - Solossa, Marthinus; Rongalaha, Johan; Palenewen, James Yoseph (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The times are developing so rapidly along with advances in technology, but genuine but fake certificates are still found in Jayapura City which are categorized as legally defective certificates. The aim of this research is to find out the factors that cause the issuance of genuine but fake certificates at the Jayapura City Land Office and to find out how to cancel genuine but fake certificates or legally defective certificates at the Jayapura City Land Office. The approach method used in this research is the normative juridical approach, namely an approach that refers to laws, library materials, written regulations or other secondary legal materials. The results of this research reveal that the factors that cause the issuance of genuine but fake certificates at the Jayapura City Land Office are 2 (two) main things, namely the first is from the applicant himself with dishonesty by making fake documents from blank signatures to the parties involved. adjacent to the land, in other words it can be said that the applicant had bad intentions from the start with the intention of deceiving the land office by entering false data, secondly from the Land Office itself because of administrative legal defects such as procedural errors, errors in the application of statutory regulations. -invitations, errors in the subject of rights, errors in types of rights, errors in area calculations, overlapping land rights, incorrect juridical data or physical data or other errors of an administrative nature. Meanwhile, the method for canceling a genuine but fake certificate or a legally defective certificate at the Jayapura City Land Office can be done by applying by the party concerned with a court decision which has permanent legal force.